2018
DOI: 10.1152/japplphysiol.00686.2017
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol regulates blood pressure by enhancing AMPK signaling to downregulate a Rac1-derived NADPH oxidase in the central nervous system

Abstract: Resveratrol is a polyphenol with pleiotropic effects against oxidative damage that has been widely implicated in lowering hypertension risk. The purpose of this study was to determine whether improve nitric oxide (NO) release in the brain, either through the activation of AMP-activated protein kinase (AMPK) or reduced Ras-related C3 botulinum toxin substrate 1 (Rac1)-induced reactive oxygen species (ROS) generation, thereby reducing blood pressure (BP) in rats with fructose-induced hypertension. The rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Oxidative stress can be defined as increased bioactivity of ROS relative to antioxidant defences [37]. In accordance with our present findings, our previous studies demonstrated that resveratrol decreases BP better than rosuvastatin, abolishes ROS generation, and enhances activity of the ERK1/2-RSK-nNOS pathway by activating AMPK to negatively regulate Racl-induced NADPH oxidase levels in the NTS during oxidative stress-associated hypertension [38].…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative stress can be defined as increased bioactivity of ROS relative to antioxidant defences [37]. In accordance with our present findings, our previous studies demonstrated that resveratrol decreases BP better than rosuvastatin, abolishes ROS generation, and enhances activity of the ERK1/2-RSK-nNOS pathway by activating AMPK to negatively regulate Racl-induced NADPH oxidase levels in the NTS during oxidative stress-associated hypertension [38].…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, a recent study demonstrated reduced activation of NADPH oxidase/ROS/NF‐κB pathways in human fibroblast‐like synoviocytes after resveratrol treatment, leading to the suppression of particulate matter air pollution‐induced COX‐2 expression and PGE2 release . Other studies have demonstrated the regulatory effect of resveratrol on the expression of NADPH oxidase . Therefore, the observed reduction in NADPH oxidase levels demonstrated with resveratrol is consistent with reduced inflammatory bone loss caused by CIS.…”
Section: Discussionmentioning
confidence: 57%
“…56 Other studies have demonstrated the regulatory effect of resveratrol on the expression of NADPH oxidase. [57][58][59][60] Therefore, the observed reduction in NADPH oxidase levels demonstrated with resveratrol is consistent with reduced inflammatory bone loss caused by CIS.…”
Section: Discussionmentioning
confidence: 64%
“…Collectively, these pieces of evidence show that the antioxidant effect of rosiglitazone and AICAR is mediated by AMPK-dependent inhibition of NADPH oxidase [216]. is was furthered by different other studies using resveratrol [194,217,218]. us, AMPK-dependent activation of NADPH oxidase and consequent reduction of ROS generation play an immense role in the antioxidant effect of AMPK activators.…”
Section: Ampk and Oxidative Stressmentioning
confidence: 90%